“Diseño de un sistema de gestión de seguridad y salud ocupacional para la empresa de telecomunicaciones QUICKLYNET S.A”. - Loachamin Gualotuña, Kevin Daniel (2021)
The design of a system can be applied to any size and type of company, it does not establish specific criteria for the control of occupational health and safety risk factors, but rather gives guidelines to meet the requirements that each company requires, the The design of this system will provide well-being and security for the employees of Quicklynet SA, considering that the worker is the most valuable part of a company. This research is mainly based on identifying risks in order to reduce them in order to improve the work environment and guarantee the health of workers. This thesis work will be developed with field research, which will serve in the identification phase of risk factors. The information will be collected through surveys applied to workers; which will serve as a starting point to obtain real data, through a correct occupational health and safety management model, it is possible to obtain an effective control of occupational risks that exist in the production process, this project benefits both its leaders and its workers giving them more confidence in their activities and this is reflected in the quality of work of each one of them.